2008
DOI: 10.2337/db07-0830
|View full text |Cite
|
Sign up to set email alerts
|

Nonobese Diabetic (NOD) Mice Congenic for a Targeted Deletion of 12/15-Lipoxygenase Are Protected From Autoimmune Diabetes

Abstract: OBJECTIVE-12/15-lipoxygenase (12/15-LO), one of a family of fatty acid oxidoreductase enzymes, reacts with polyenoic fatty acids to produce proinflammatory lipids. 12/15-LO is expressed in macrophages and pancreatic ␤-cells. It enhances interleukin 12 production by macrophages, and several of its products induce apoptosis of ␤-cells at nanomolar concentrations in vitro. We had previously demonstrated a role for 12/15-LO in ␤-cell damage in the streptozotocin model of diabetes. Since the gene encoding 12/15-LO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 55 publications
10
89
1
Order By: Relevance
“…Collectively, these findings suggest that iPLA 2 ␤ deficiency mitigates polarization of macrophages toward an M1 phenotype. (42)(43)(44)(45). Consistent with this, we find that both ALOX-12 ( Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Collectively, these findings suggest that iPLA 2 ␤ deficiency mitigates polarization of macrophages toward an M1 phenotype. (42)(43)(44)(45). Consistent with this, we find that both ALOX-12 ( Fig.…”
Section: Resultssupporting
confidence: 79%
“…12-S-hydroxyeicosatetraenoic acid) and is not detected in healthy islets but is in both T1D and T2D islets (42), is induced to a much higher level in WT macrophages than in iPLA 2 ␤-deficient macrophages. The importance of 12-LO in promoting macrophage recruitment and activation and causing detrimental effects on islet function and ␤-cell mass is supported by the reports that deletion of 12-LO protects against T1D development (44,45). Our findings, therefore, suggest that iPLA 2 ␤ activation, in addition to skewing macrophage polarization toward M1, may also preserve functionality of downstream lipidmetabolizing enzymes.…”
Section: Discussionsupporting
confidence: 73%
“…Deletion of 12-lipoxygenase protects mice against hyperglycaemia induced with low dose streptozotocin. In the NOD mouse, 12-lipoxygenase deletion confers a near complete protection against type 1 diabetes and also reduces immune cell activation [17,23]. Interestingly, two independent groups have shown that 12-lipoxygenase activation also participates in high-fat-induced insulin resistance and adipose tissue inflammation [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Direct addition of 12-S-HETE can impair beta cell function or can lead to loss of human beta cell viability [13,15,16,[19][20][21][22]. Recent evidence indicates that increased expression of 12-lipoxygenase in islets is a common feature of both rodent and human models of type 1 and type 2 diabetes [11,13,15,17,22]. Deletion of 12-lipoxygenase protects mice against hyperglycaemia induced with low dose streptozotocin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation